Direction selective neurons responsive to horizontal motion in a crab reflect an adaptation to prevailing movements in flat environments - Scarano, María Florencia (2020)
All animals need information about the direction of motion to be able to track the trajectory of a target (prey, predator, cospecific) or to control the course of navigation. This information is provided by direction selective (DS) neurons, which respond to images moving in a unique direction. DS neurons have been described in numerous species including many arthropods. In these animals, the majority of the studies have focused on DS neurons dedicated to processing the optic flow generated during navigation. In contrast, only a few studies were performed on DS neurons related to object motion processing. The crab Neohelice is an established experimental model for the study of neurons involved in visually- guided behaviors. Here, we describe in male crabs of this species a new group of DS neurons that are highly directionally selective to moving objects. The neurons were physiologically and morphologically characterized by intracellular recording and staining in the optic lobe of intact animals. Because of their arborization in the lobula complex, we called these cells lobula complex directional cells (LCDCs). LCDCs also arborize in a previously undescribed small neuropil of the lateral protocerebrum. LCDCs are responsive only to horizontal motion. This nicely fits in the behavioral adaptations of a crab inhabiting a flat, densely crowded environment, where most object motions are generated by neighboring crabs moving along the horizontal plane.